Interaction human-robot : a methodological proposal to evaluate actions performed by robots to elderly - Pereira, Cristina (2020)
Background Developing new assistive technologies is a challenge for an ageing society and a possible response to the needs of older people in the care process and a challenge to promote autonomous living. The interaction between elderly and robots may depend on the choice of activities that robots can developed and the how important it is for older people. Social Assistive Robots can contribute to a positive impact in elderly well-being and active ageing. Methods 31 elderly residents (10 men and 21 women) in a Portuguese nursing home were interviewed about their routines and interests. They were also assessed during 6 weeks, to evaluate interactions and activities initiative and involvement, using an scale adapted by authors from a Bertram and Pascal scale. This assessment was made by direct observation. The professionals and the director in the nursing home were also interviewed. Research results The adopted methodology allowed to identify the needs and interests of the elderly, and to classify the participants on the levels of social interactions, initiative and involvement in activities and social participation. Conclusions Some social, cognitive and physical activities were selected to be developed by a socially assisted robot and the evaluation process used in this research methodology will be used to evaluate the results of the intervention with a robot in social assistive domains, developed in a European Project INTERREG (EUROAGE).